2021
DOI: 10.1111/1467-6427.12332
|View full text |Cite
|
Sign up to set email alerts
|

‘Living in a Zoom world’: Survey mapping how COVID‐19 is changing family therapy practice in the UK

Abstract: Following the COVID‐19 pandemic, psychological therapies rapidly moved online in mid‐2020. The Association for Family Therapy and Systemic Practice in the UK (AFT) surveyed the attitudes and practices of systemic therapists in the UK in early October 2020, exploring members’ views and gathered information about ongoing needs. A sample of 312 people were included in a mixed methods analysis. In total, 65% of respondents felt their overall experience of using online video technology professionally was positive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 19 publications
3
63
0
Order By: Relevance
“…ICTs have allowed practitioners to provide continuity of care (Gentry et al, 2021;Waller et al, 2020), and maintain the therapeutic relationship during COVID-19 (McKenny et al, 2021;Moring et al, 2020). ICTs removed client barriers related to transportation, work commitments, and childcare (Hopkins & Pedwell, 2021), and improved client attendance and engagement (McKenny et al, 2021). Many practitioners intend to continue providing digital services to some degree beyond COVID-19 (Gentry et al, 2021).…”
Section: Covid-19 Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…ICTs have allowed practitioners to provide continuity of care (Gentry et al, 2021;Waller et al, 2020), and maintain the therapeutic relationship during COVID-19 (McKenny et al, 2021;Moring et al, 2020). ICTs removed client barriers related to transportation, work commitments, and childcare (Hopkins & Pedwell, 2021), and improved client attendance and engagement (McKenny et al, 2021). Many practitioners intend to continue providing digital services to some degree beyond COVID-19 (Gentry et al, 2021).…”
Section: Covid-19 Contextmentioning
confidence: 99%
“…The pandemic has exacerbated existing inequities by sharpening the "digital divide" among clients (Farkas & Romaniuk, 2020, p. 1). Clients face barriers to remote services due to matters such as poverty/financial, privacy, and childcare issues, rural settings, lack of technology literacy, psychiatric diagnoses, and age (Canady, 2020;Liberati et al, 2021;McKenny et al, 2021;Perrin et al, 2020;Pierce et al, 2020;Razai et al, 2020;Simpson et al, 2021;Wells et al, 2020). In this article, we provide a unique analysis of practitioners' and clients' perspectives before and after the onset of COVID-19.…”
Section: Covid-19 Contextmentioning
confidence: 99%
“…For example, research suggests that very young children, older generations, clients lacking motivation for treatment or families with lower social economic status or education might experience more difficulty handling the required technology and/or may be more difficult to engage in VC sessions (Crum & Comer, 2016 ; Florean et al, 2020 ; Matheson et al, 2020 ). Some adolescents may further feel screenshy (Burgoyne & Cohn, 2020 ; Mc Kenny et al, 2021 ). Working with multi-stressed families may involve multiple of these challenges, as these families may be more likely to have a low social economic status, lack motivation, and treatment may involve working with the children or adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Again, interruptions may be more frequent when interacting with multiple family members in the same session. At the same time, advantages have been mentioned as well; clients may experience an increased feeling of control, safety or empowerment and the flexibility of VC may improve session attendance (Mc Kenny et al, 2021 ; Sibley et al, 2017 ; Simpson & Reid, 2014 ). Thus, although several challenges can be hypothesized when using VC in a systemic context with multi-stressed families, more research is needed to understand the feasibility and effectiveness of family-based VC.…”
Section: Introductionmentioning
confidence: 99%
“…In a narrative review of mostly North American literature, advantages were identified, including convenience, increased acceptance and adherence, cost efficiencies, enhancements in communication, and other therapy benefits [ 10 ]. Furthermore, factors contributing to the positive evaluation of web-based care by clients included meeting needs in a timely and effective manner [ 11 ], a more egalitarian therapeutic alliance [ 12 ], and an increased sense of being in control [ 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%